ANALYSIS OF THE RELATIONSHIP BETWEEN THE MARKET VALUE / BOOK VALUE AND APPLICATION OF ACCOUNTING STANDARDS (IMPAIRMENT OF ASSETS) - Vilchez Olivares, Percy Antonio (2011)
This article presents an analysis of the metric Market Value / Book Value of companies listed on the Lima Stock Exchange, and as this relationship is considered by the International Accounting Standard for Impairment of Assets in the process of evaluating signs of deterioration by the company. In this regard, the article describes the conceptual and normative aspects of the Standard Impairment of Assets, Methodology for the implementation of Impairment of Assets, an analysis of the results of the relation Market Value / Book Value to submitted by companies listed on the Lima Stock Exchange, and its impact on establishing evidence of deterioration in the business.